Analisis Kredit Macet Terhadap Kinerja Keuangan Koperasi Simpan Pinjam Swasti Sari Cabang Kota Kupang (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze bad debts on the financial performance of the Kupang City Branch of the Swasti Sari Savings and Loan Cooperative. The research method used is descriptive quantitative, with data analysis techniques using bad debt analysis and financial performance analysis by measuring financial ratios such as liquidity, solvency and profitability ratios. The data used in this study is secondary data in the form of financial statements of the Swasti Sari Saving and Loan Cooperative, Kupang City Branch for a period of 5 years from 2019-2023. The results showed that bad debts at the Kupang City Branch of the Swasti Sari Savings and Loan Cooperative were caused by the inability of cooperative members to pay off their obligations so that the cooperative's receivables became difficult to collect and had an impact on the cooperative's financial performance as measured by the liquidity ratio from 2019 to 2023 which decreased because the cooperative's cash decreased and its receivables increased, the Solvency Ratio indicates an increase in risk due to increased debt without balanced asset growth. The Profitability Ratio shows a decrease in net income which affects the operational sustainability of the Kupang City Branch of the Swasti Sari Savings and Loan Cooperative. The results of this study provide recommendations for the Kupang City Branch of the Swasti Sari Saving and Loan Cooperative in overcoming the risk of bad credit, namely taking a rescheduling, reconditioning, and restructuring approach, applying prudential principles, conducting regular monitoring and monitoring of financial performance and credit risk so that cooperatives can make quick and appropriate decisions to maintain financial stability and operational sustainability.